Gambaran Tingkat Pengetahuan, Sikap, dan Tindakan Tenaga Kesehatan tentang Penggunaan Alat Pelindung Diri dalam Penanganan Kejadian Covid-19 di Puskesmas Kawangkoan - Lolowang, Erika Venda; Pinontoan, Odi R.; Sondakh, Ricky C. (Sam Ratulangi University, 2022)
Alat Pelindung Diri ialah alat yang dapat mengamankan individu yang mampu melepaskan sebagian atau seluruh tubuhnya dari risiko yang diperkirakan di lingkungan kerja. Motivasi di balik ulasan ini adalah untuk menggambarkan tingkat informasi tentang pandangan dan aktivitas pekerja kesehatan terkait penggunaan alat pertahanan individu dalam menangani kasus Coronavirus di Pusat Kesehatan Kawangkoan, menggunakan pemeriksaan kuantitatif dengan metode ekspresif. Contoh 48 tenaga kesejahteraan yang mendapat polling tentang APD. Konsekuensi dari tinjauan ini menunjukkan bahwa sebagian besar responden berusia 24 – 59 tahun, pendidikan terakhir D3 – S2, dan masa kerja 1-25 tahun. Konsekuensi dari tinjauan ini menunjukkan bahwa pekerja kesejahteraan di Pusat Kesejahteraan Kawangkoan memiliki informasi paling bagus, perspektif hebat, dan aktivitas hebat. Akhir dari review ini adalah informasi, perspektif dan aktivitas pekerja kesejahteraan dalam penggunaan peralatan pertahanan individu dalam menghadapi virus Corona di Pusat Kesehatan Kawangkoan sangat bagus. Kata Kunci : Pengetahuan, Sikap, Tindakan, Alat Pelindung Diri Covid-19 ABSTRACTIndividual Defensive Hardware, hereinafter shortened as PPE, is an instrument that can secure an individual whose capacity is to detach part or all of the body from expected risks in the working environment. Individual defensive gear (PPE) is a gadget planned as a boundary against the entrance of substances, strong, fluid, or air particles to shield contamination or sickness. The motivation behind this review was to depict the degree of information on the perspectives and activities of wellbeing laborers in regards to the utilization of individual defensive gear in taking care of Coronavirus occasions at the Kawangkoan Wellbeing Center, utilizing quantitative examination with an expressive methodology. An example of 48 wellbeing laborers who got a poll about PPE. The consequences of this review demonstrate that the greater part of the respondents are matured 24 – 59 years, the last training is D3 – S2, and the length of work is 1-25 years. The consequences of this review demonstrate that the wellbeing laborers at the Kawangkoan Wellbeing Center have the most great information, great perspectives and great activities. The finish of this review is that the information, perspectives and activities of wellbeing laborers in the utilization of individual defensive gear in dealing with Coronavirus at the Kawangkoan Wellbeing Center are great. Keywords : Knowledge, Attitude, Action, Personal Protective Equipment Covid-19